2022
DOI: 10.1002/adma.202107888
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Quantum Dot Solar Cells: Progressive Deposition Techniques and Future Prospects on Large‐Area Fabrication

Abstract: large-area fabrication without compromising the power conversion efficiency (PCE) always comes with new and unexpected challenges even for well-studied and well-optimized laboratory-scale PV technologies. For instance, non-concentrated monocrystalline silicon solar cells have reached a record 26.1% PCE, [1] but the efficiencies of most recent commercial panels are typically only up to about 22% (e.g., SunPower's Maxeon 3 panels: 22.8%, LG's Neon R: 22%, Panasonic's EverVolt: 21.7%). [2] Apart from the technica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 263 publications
0
48
0
Order By: Relevance
“…Thanks to the significant efforts for scaling-up techniques, feasible and promising methods have been successfully developed, such as blade coating, printing, spray coating and slot die. [43] For example, slot die-printed PSCs with an area of 17 cm 2 realized a high PCE of 20.4%, which is very impressive and confirms the prospect of slot die method for the fabrication of large area device with high performance. [102] The scaling up techniques are still in the development stage and more efforts are expect for further refinement of these methods, especially with the incorporation of QDs.…”
Section: Discussionmentioning
confidence: 54%
“…Thanks to the significant efforts for scaling-up techniques, feasible and promising methods have been successfully developed, such as blade coating, printing, spray coating and slot die. [43] For example, slot die-printed PSCs with an area of 17 cm 2 realized a high PCE of 20.4%, which is very impressive and confirms the prospect of slot die method for the fabrication of large area device with high performance. [102] The scaling up techniques are still in the development stage and more efforts are expect for further refinement of these methods, especially with the incorporation of QDs.…”
Section: Discussionmentioning
confidence: 54%
“…With the rational design of device structure and processing techniques, the realization of PQDs involved tandem solar cells will finally come true. Alternatively, though the large-scale fabrication of PQD solar cells has not been reported, it seems very promising for the layer-by-layer solution process, which is compatible with the large-area blade-coating, slot-die, and dip-coating techniques . The thickness tolerance of a QD films is improved by a P–N homojunction structure, as we have elaborated in section .…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the unexpansive fabrication processes, the upscaling techniques and the gained maturity over the last decade, it is believed that colloidal QD PV technology is moving forward toward commercialization. [269,270] Broader Context of the Bandgap Tuning in Single Junction SC: From a universal perspective, Peters and Buonassisi established a correlation between lab-measured efficiencies and energy yield based on satellite data for various single junction PV technologies with different bandgaps. [271] It was found that the bandgap noticeably influenced the energy yield.…”
Section: Bandgap Tuning In Single Junction Sc Technologiesmentioning
confidence: 99%